2013
DOI: 10.1371/journal.pone.0070665
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of the Phenylpropanoid Pathway Enhances the Antioxidant Capacity of Saussurea involucrata

Abstract: The rare wild species of snow lotus Saussurea involucrata is a commonly used medicinal herb with great pharmacological value for human health, resulting from its uniquely high level of phenylpropanoid compound production. To gain information on the phenylpropanid biosynthetic pathway genes in this critically important medicinal plant, global transcriptome sequencing was performed. It revealed that the phenylpropanoid pathway genes were well represented in S. involucrata. In addition, we introduced two key phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…When constitutively expressed in maize, ZmMYB-IF35 promotes the accumulation of ferulic and chlorogenic acids (Dias and Grotewold, 2003). Meanwhile, constitutive expression in tobacco, potato, tomato, and snow lotus (Saussurea involucrata) of the potato genes StAN1, StMTF1, and PAP1, as well as that of AtMYB12, increases chlorogenic acid content (Luo et al, 2008;Rommens et al, 2008;Payyavula et al, 2013;Qiu et al, 2013). Both A. thaliana AtMYB4 and S. miltiorrhiza SmMYB39 belong to R2R3-MYB subgroup 4 ( Figure 3).…”
Section: Phenolic Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…When constitutively expressed in maize, ZmMYB-IF35 promotes the accumulation of ferulic and chlorogenic acids (Dias and Grotewold, 2003). Meanwhile, constitutive expression in tobacco, potato, tomato, and snow lotus (Saussurea involucrata) of the potato genes StAN1, StMTF1, and PAP1, as well as that of AtMYB12, increases chlorogenic acid content (Luo et al, 2008;Rommens et al, 2008;Payyavula et al, 2013;Qiu et al, 2013). Both A. thaliana AtMYB4 and S. miltiorrhiza SmMYB39 belong to R2R3-MYB subgroup 4 ( Figure 3).…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Some R2R3-MYB transcription factors regulate the synthesis of more than one class of phenylpropanoid-derived compounds. Examples include MdMYB3 (anthocyanin and flavonol), AtMYB4 (monolignol and phenolic acid), AtMYB12 (flavonol and phenolic acid), PAP1 (monolignol, anthocyanin, proanthocyanidin, flavonols, and phenolic acid), FaMYB1 (anthocyanin, proanthocyanidins, and flavonol), VvMYB5a (anthocyanin, proanthocyanidin, flavonol), VvMYB5b (anthocyanin and proanthocyanidin), StAN1 (anthocyanin, flavonols, and phenolic acid), StMTF1 (anthocyanin, flavonols, and phenolic acid), and ROSEA1 (anthocyanin and phenolic acid) (Aharoni et al, 2001;Deluc et al, 2006Deluc et al, , 2008Stracke et al, 2007;Luo et al, 2008;Rommens et al, 2008;Zuluaga et al, 2008;Li et al, 2010;Zhang et al, 2010;Paolocci et al, 2011;Payyavula et al, 2013;Qiu et al, 2013;Vimolmangkang et al, 2013;Wang et al, 2013). MdMYB3, AtMYB12, FaMYB1, and VvMYB5b regulate the expression of different phenylpropanoid-derived compound structural genes such as CHS, CHI, F3H, FLS, F3 0 5 0 H (encoding flavonoid 3 0 5 0hydroxylase), DFR, ANS, ANR, LAR, GT (encoding glycosyl transferase), HCT (encoding hydroxycinnamoyl CoA shikimate/ quinate transferase), C3H (encoding p-coumaroyl ester 3-hydroxylase), and HQT (encoding hydroxycinnamoyl CoA quinate transferase) (Aharoni et al, 2001;Stracke et al, 2007;Deluc et al, 2008;Luo et al, 2008;Paolocci et al, 2011;Vimolmangkang et al, 2013).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…belongs to the Asteraceae family of the genus Saussurea, which is used to treat rheumatoid arthritis and regulate the menstrual cycle [1]. Pharmacologic studies show that many medicinal values of S. involucrate are derived from its flavonoids, and these include anti-neoplastic [2], anti-arthritic [3], anti-oxidative, anti-aging [4,5], and anti-fatigue [6] properties. Flavonoids also play an important role in blocking melanin deposition and skin whitening products.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the diverse functions of these TFs it becomes extremely difficult to give explanations to the intricate role of bHLH, MYB, MYC and TTG1 TFs. PAP1 (production of anthocyanin pigment1) being well described for its involvement in the anthocyanin biosynthetic pathway 82 but Sekhon et al 83 and Pourtau et al 84 have also reported PAP1 and PAP2 to be involved in senescence induced by pollination prevention in maize and sugar application in Arabidopsis, respectively. Hence, the expression pattern of PAP1 in O. sanctum may be due to some stress induced at the onset of winter season in November and December as Ocimum is a plant of tropics.…”
Section: Discussionmentioning
confidence: 99%